Clinical trials of vitamin-mineral supplementations in people with epilepsy: A systematic review. Issue 5 (May 2021) - Asadi-Pooya, Ali A.; Simani, Leila
Summary: Objective: The purpose of the current study was to systematically review the literature on the clinical trials of vitamin-mineral supplementations in people with epilepsy (PWE) to treat their seizures. Methods: MEDLINE and Scopus from inception to August 25, 2020 were searched for related published manuscripts. The search keywords included "vitamin or folate or folic acid or biotin or thiamine or carnitine or zinc or manganese or selenium or omega-3 fatty acid or linoleic acid or micronutrient or trace element or supplementation" AND "epilepsy or seizure". Results: We could identify 26 related articles. Seventeen studies provided class 2 of evidence and the rest provided class 3 of evidence. Eight studies investigated polyunsaturated fats, seven groups studied folic acid, four studies explored the effects of vitamin D, two investigated vitamin E, and three others studied multivitamin cocktails. There was one study on zinc and one on selenium. There is some evidence on the efficacy of polyunsaturated fats in treating seizures in PWE. The evidence on the efficacy of multivitamin cocktails in adults is promising. Conclusion: High quality data on the efficacy of nutritional (vitamins-minerals) supplementations in treating seizures in PWE is scarce; however, designing future clinical trials of polyunsaturated fatty acid supplementation for drug-resistant seizures in adults with focal epilepsy and in children, and also multivitamin supplementations in adults with focal epilepsy seems reasonable and promising. Such clinical trials should be well-designed, randomized, and placebo controlled, with enough sample size and adequate follow-up of 12 months or more.